2022
DOI: 10.1177/00220221211060441
|View full text |Cite
|
Sign up to set email alerts
|

A Cross-Cultural Investigation of Basic Psychological Need Satisfaction at Work in an Indigenous and Non-Indigenous Australian Sample Across Occupation Types

Abstract: Self-determination theory (SDT) posits universality without cross-cultural uniformity of the three basic psychological needs (autonomy, competence, and relatedness) which have been associated with desirable job outcomes. Yet these promising directions in theory and research have not been extended to Indigenous samples and different occupational types. This is unfortunate as Indigenous peoples globally remain the most disadvantaged on all socio-economic indicators, including employment. This study adopted a str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 59 publications
(94 reference statements)
0
4
0
Order By: Relevance
“…BPNs have been studied in numerous contexts, including leadership (Slemp et al ., 2018), employee well-being (Olafsen and Deci, 2020), motivation and productivity (Rietveld et al ., 2022), employees performance (Good et al ., 2022), satisfaction at work and job outcome (Magson et al ., 2022). For example, Slemp et al .…”
Section: Theoretical Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…BPNs have been studied in numerous contexts, including leadership (Slemp et al ., 2018), employee well-being (Olafsen and Deci, 2020), motivation and productivity (Rietveld et al ., 2022), employees performance (Good et al ., 2022), satisfaction at work and job outcome (Magson et al ., 2022). For example, Slemp et al .…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…employees performance (Good et al, 2022), satisfaction at work and job outcome (Magson et al, 2022). For example, Slemp et al (2018) found that leadership autonomy support correlates strongly with autonomous work motivation, enabling well-being and better performance.…”
Section: Sies Motivation and Bpnsmentioning
confidence: 99%
“…With regard to organizational climate, all three psychological needs were significantly and positively associated with positive leader behavior and perceived organizational support while the fit between employee and work environment was significantly and positively linked only to the satisfaction of autonomy needs [22]. In a more recent study in Australia, satisfaction of autonomy and competence needs were associated with less job ambiguity while relatedness needs were associated with greater resilience at work [23]. In a review of daily diary studies, Coxen et al [24] confirmed that different outcomes are associated with different needs but as importantly, the study also highlighted the fact that significant variation within employees over time merits examining needs satisfaction frequently on a weekly or daily basis.…”
Section: How Are Basic Psychological Needs Relevant At Work?mentioning
confidence: 91%
“…With regard to organizational climate, all three psychological needs were significantly and positively associated with positive leader behavior and perceived organizational support while the fit between employee and work environment was significantly and positively linked only to the satisfaction of autonomy needs [24]. In a more recent study in Australia, satisfaction of autonomy and competence needs were associated with less job ambiguity while relatedness needs were associated with greater resilience at work [25]. In a review of daily diary studies, Coxen et al [26] confirmed that different outcomes are associated with different needs.…”
Section: How Are Basic Psychological Needs Relevant At Work?mentioning
confidence: 91%